GFRP Stay in Place (SIP) Flexible Formwork for Curved Slabs - Gaur, Shivang (My University, 2018)
One of the important purpose of construction research is to develop a creative, ingenious, economical and efficient method of construction. Stay-in-place (SIP) formwork is such a system that is not required to be removed upon hardening of concrete. SIP structural formwork is a permanent participating formwork system which is structurally integrated with concrete. It acts as self-supporting formwork during construction and remains to act as reinforcement after the concrete hardens. This research is in continuation with previous study which investigated the role of FRP stay-in-place formwork for concrete straight slabs. In this study aim was to check the behavior of GFRP planks as SIP formwork as well as reinforcement for curved slabs. Experimental investigation regarding the suitability of the plank as SIP formwork for curved slab was done in two stages- casting stage testing and cured concrete flexural testing. In casting stage testing, sand and concrete loading tests were conducted to check if the planks has sufficient strength and stiffness for obtaining desirable curvature of slab. Performance of plank was tested as formwork for both straight and curved slabs In the second stage testing the role of SIP formwork as reinforcement for curved slabs was investigated through cyclic flexural tests. For this test three slabs were casted out of which two are curved and one is straight with two types of bond treatments- aggregate bonding and adhesive bonding were compared. Ultimate load carrying capacity, deflection and strains level in GFRP and concrete were measured under two-point cyclic loading. Acoustic emission technique was used to monitor the cracks development during flexural testing. Finally, numerical validation of the experimental data was performed using non-linear finite elements method. A three-dimensional finite element model was prepared using software ATENA to simulate the behaviour of the bond treated GFRP-concrete interface. Load carrying capacity of curved slab is around 25% higher than straight slabs. From the failure mode of all the three slabs, it was concluded that failure mode is brittle in case of both straight slabs and curved slabs. This study demonstrates that the bond treated FRP plank has the potential to serve as formwork and as tensile reinforcement for appropriately sized curved slabs concrete slabs provided the ductility issue is solved.
Keywords: GFRP; CURVED SLABS; FEM SIMULATION; AESTHETIC; CONCRETE